Bronchoscopic device intervention in chronic obstructive pulmonary disease. Issue 2 (March 2019) - Dunlap, Daniel G.; Semaan, Roy; Riley, Craig M.; Sciurba, Frank C.
Abstract : Purpose of review: Chronic obstructive pulmonary disease is a heterogeneous syndrome associated with varying degrees of parenchymal emphysema and airway inflammation resulting in decreased expiratory flow, lung hyperinflation, and symptoms leading to decreased exercise tolerance and quality of life. Impairment in lung function and quality of life persists following guideline-based medical therapy, thus surgical and minimally invasive bronchoscopic approaches were developed to address this unmet need. We offer a narrative review of the available technologies. Recent findings: Although lung volume reduction surgery has been shown to improve survival in appropriately selected patients, it is infrequently performed. Less invasive bronchoscopic procedures have thus been explored including endobronchial valves, coils, lung sealant, thermal vapor, and other airway approaches. Selection criteria including severity of physiologic and radiographic impairment, degree of lung hyperinflation, presence of intact fissures, type of symptoms, and presence of comorbidities are critical in selecting appropriate candidates. Summary: Recent advances in minimally invasive approaches to lung volume reduction have offered alternatives to surgical approaches. Two endobronchial valve devices are Food and Drug Administration approved for clinical use, and investigations into alternative bronchoscopic therapies to treat both emphysema and chronic bronchitis have been performed or are currently underway. Notably, each of these treatments requires unique selection criteria and thus a personalized approach to treatment.